2021
DOI: 10.1136/rmdopen-2021-001580
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies in COVID-19: a meta-analysis and systematic review

Abstract: BackgroundMany studies reported high prevalence of antiphospholipid antibodies (aPL) in patients with COVID-19 raising questions about its true prevalence and its clinical impact on the disease course.MethodsWe conducted a meta-analysis and a systematic review to examine the prevalence of aPL and its clinical impact in patients with COVID-19.Results21 studies with a total of 1159 patients were included in our meta-analysis. Among patients hospitalised with COVID-19, the pooled prevalence rate of one or more aP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
103
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 44 publications
6
103
1
5
Order By: Relevance
“…Notably, the coagulopathy found in critically ill COVID-19 patients bears some similarities to the catastrophic antiphospholipid syndrome, which presented with multiple-organic thrombosis [34] , [35] . According to recent studies, there is a questionable association between aPLs and major thrombotic events considering the transient and low titers of aPLs in some COVID-19 patients [36] , [37] , [38] , [39] , [40] . Taha et al [39] conducted a meta-analysis and a systematic review including 21 studies and found that COVID patients with severe disease presented with a higher prevalence of aPL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the coagulopathy found in critically ill COVID-19 patients bears some similarities to the catastrophic antiphospholipid syndrome, which presented with multiple-organic thrombosis [34] , [35] . According to recent studies, there is a questionable association between aPLs and major thrombotic events considering the transient and low titers of aPLs in some COVID-19 patients [36] , [37] , [38] , [39] , [40] . Taha et al [39] conducted a meta-analysis and a systematic review including 21 studies and found that COVID patients with severe disease presented with a higher prevalence of aPL.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, there is a questionable association between aPLs and major thrombotic events considering the transient and low titers of aPLs in some COVID-19 patients [36] , [37] , [38] , [39] , [40] . Taha et al [39] conducted a meta-analysis and a systematic review including 21 studies and found that COVID patients with severe disease presented with a higher prevalence of aPL. However, there was no association between aPL positivity and disease outcomes, including thrombosis [39] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher prevalence of aPL reported in other studies with COVID-19 patients versus their own control population may be due to the lower mean age of the control populations with which they were compared, which evidently have a lower prevalence of autoantibodies. In the meta-analysis, carried out by Taha and Samavati, in which the prevalence of aPL in COVID-19 patients was assessed by evaluating 21 publications, all studies reported prevalence without a control group [ 22 ]. Therefore, it must be assumed that in these 21 studies, the comparisons were made using the aPL prevalence published in the literature, which are based on blood donor cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of aPL in COVID-19 patients, with or without thrombotic events, varies between 21–70%, according to the methods used in its detection and whether the presence of LA is assessed or not [ 19 , 20 , 21 ]. In a recent meta-analysis that included 21 studies, the pooled prevalence rate of one or more aPL (aCL or anti-B2GPI IgG/M/A, or anti-PS/PT, or LA) was 46.8% [ 22 ]. In our country, the prevalence of aPL in COVID-19 patients at the time of hospital admission, excluding LA (aCL or anti-B2GPI, or anti PS/PT), is 23,6% which is higher than the 6.1% described in the control group of 201 blood donors [ 21 ] and the 5–5.5% described in other studies [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%